Structural and functional features of bone tissue and their significance in osteoregeneration - Chelpanova , I.V. (Морфологія / Morphologia / Morfologìâ, 2025)
The aim of this study was to investigate the structural and functional characteristics of bone tissue and their significance for osteoregeneration. To achieve this goal, we reviewed relevant domestic and international scientific and medical literature. Results: Bone tissue is a composite material with mineral crystals embedded in a collagen matrix; its mechanical properties depend on the interaction between these components. Bone possesses the capacity for lifelong remodeling, adapting to internal and external factors, with age-related remodeling influencing its mechanical properties. The collagen (I), forming a triple helix structure, is the most abundant protein in the bone matrix, providing structural support and mechanical strength. Non-collagenous proteins constitute approximately 10-15% of the total protein content in bone tissue and participate in mineralization, remodeling, and cell signaling, as well as regulating the activity of osteoblasts and osteoclasts. Major non-collagenous proteins include osteocalcin, osteonectin, osteopontin, bone sialoprotein, and others. Together, these proteins form a highly organized and dynamic structure that supports the mechanical properties of bone and governs the complex processes of bone formation, maintenance, and remodeling. The inorganic component of bone is predominantly composed of minerals, with calcium and phosphate being the most important. These minerals form hydroxyapatite crystals (Ca₁₀(PO₄)₆(OH)₂), which are embedded within the collagen matrix. Hydroxyapatite provides hardness and rigidity, contributing to the structural strength of bone and constituting approximately 60-70% of its dry weight. The presence of hydroxyapatite is crucial not only for maintaining the structural integrity of bone but also for facilitating key regenerative processes such as osteoinduction and osteoconduction. The complex interplay between osteoblasts, osteoclasts, and other regulatory factors ensures that bones remain functional and strong, responding to the demands of growth, aging, and mechanical loading while preventing pathologies associated with bone remodeling imbalance. Histomorphometry and histomorphometry can be employed using static and dynamic methods, depending on whether the tissue is examined at a single time point or tracked over a period of time. Conclusion. A review of the scientific literature reveals some inconsistencies in understanding the structural and functional variations in bone tissue reconstruction across different clinical scenarios. A significant number of scientific studies, both experimental and clinical, are devoted to the study of osteoregeneration, but in modern conditions, correct understanding of the sequence and timing of osteogenetic regenerative processes is of particular importance. Therefore, it is justified to study the dynamics of histoarchitectural changes that occur during the healing of bone defects, which will allow the development of personalized osteoregeneration strategies adapted to the needs of a particular patient.